An Initial Study on the Effectiveness of TM Online Customer Care Service - Sukhdev Singh, Karnail Singh (2008)
The purpose of this research is to study the effectiveness of TM Online Customer Care Services at Telekom Malaysia Bhd used for rendering services to all TM customers as an alternative support or a helpdesk service. The aims are to identify the effectiveness the Online Customer Care Service and to provide recommendations for the future improvement of the system. In this study, TM customers in various types of services were surveyed and the results showed that there are four main factors that influence the effectiveness of the TM Online Customer Care Services. These factors are customers' behavior and attitude, technology and system, interactive applications and characteristics of TM Staff, and the paper discusses these factors in detail with an emphasis on the role of the TM Online Customer Care Services.